Etika Pendidik dan Peserta Didik Menurut Perspektif Al-Ghazali dan John Locke: Studi Komparasi Pemikiran Islam dan Barat - Muhammad Ghaffar Arafat Abdul Azmi; Akhmad Sodiq (Universitas Majalengka, 2026)
This study examines the ethical foundations of teacher–student relations in the thought of Al-Ghazali and John Locke, with the objective of identifying their conceptual convergences, divergences, and relevance to contemporary educational ethics. Using a qualitative library-research design, the study analyzes primary works Ihya’ Ulumuddin and Some Thoughts Concerning Education supported by peer-reviewed literature. Data were collected through documentation and analyzed using content analysis, comparative evaluation, and critical interpretation. The findings demonstrate that Al-Ghazali grounds educational ethics in spiritual purification, moral exemplarity, and disciplined learning, whereas Locke frames ethics within rational autonomy, moral habituation, and exemplary conduct grounded in empiricism. Both scholars emphasize character formation, educator integrity, and humane pedagogical relations, yet differ in their metaphysical orientations Al-Ghazali being theocentric and Locke anthropocentric–rational. The study argues that an integrative ethical model synthesizing spiritual–moral discipline and rational–empirical autonomy offers theoretical and practical relevance for addressing contemporary issues such as diminished teacher authority, erosion of student respect, and ethical challenges in digital learning environments. This research includes over sixty references and no tables, figures, or appendices.